HUBUNGAN POLA ASUH DEMOKRATIS TERHADAP KEPATUHAN SISWA DALAM MELAKSANAKAN TATA TERTIB DI SEKOLAH DASAR - Zuriatul Khairi; Yolanda Pahrul; Iis Aprinawati (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2022)
This study aims to determine how democratic parenting, how is the level of student discipline, and is there a significant relationship between democratic parenting and student discipline. In this study, there were 20 students who had democratic parenting. The sampling technique is a sampling technique, where sampling is done by giving each individual the opportunity to become a member of the sample. Data collection techniques in this study were documentation, questionnaires, and observation. The technique of data analysis was using Peasson product moment correlation analysis with a significant level of 0.05. Democratic parenting pattern with student discipline has a significant relationship where t count > t table democratic parenting with student discipline has t count 2,473, t table 1,725 ​​contribution (contribution) of 25.40% and has a fairly high level of discipline category with rxy 0.504. The results of the study show that there is a relationship between democratic parenting and discipline for the fifth grade students of SD Negeri 014 Ganting Damai.